2022
DOI: 10.1007/s11356-022-23191-6
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing agglomeration, urban form, and haze pollution

Abstract: Manufacturing agglomeration promotes rapid economic development while also causing severe environmental pollution. This paper investigates the impact and mechanism of manufacturing agglomeration on haze pollution from the Chinese city level. Furthermore, we discuss the moderating effect and threshold effect of the three urban forms of urban external shape complexity, urban compactness, and urban fragmentation on the relationship between the two. The result shows: (1) The aggregation of the manufacturing indust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…In comparison with existing literature, the regression results align with those of Ye et al (2021). Unlike the study by Wei et al (2023), which only considers manufacturing agglomeration, our analysis suggests that as manufacturing clusters advance, the agglomeration economy can contribute to reduced pollution emissions.…”
Section: Results Of Benchmark Regressionsupporting
confidence: 77%
“…In comparison with existing literature, the regression results align with those of Ye et al (2021). Unlike the study by Wei et al (2023), which only considers manufacturing agglomeration, our analysis suggests that as manufacturing clusters advance, the agglomeration economy can contribute to reduced pollution emissions.…”
Section: Results Of Benchmark Regressionsupporting
confidence: 77%
“…The improvement effect of green credit policies on air quality also proves this conclusion [26]. In addition, green finance is also beneficial for improving ecological welfare performance and promoting industrial green transformation and development [27,28]. Research based on the Yangtze River Economic Belt has shown a high degree of coupling and coordination between green finance and industrial green development [29], which provides indirect evidence for green finance to improve urban haze.…”
Section: Introductionmentioning
confidence: 82%
“…The single-index measurement employs statistical or remote sensing data to calculate a comprehensive index characterizing UC. For instance, Wei et al [ 26 ] measured UC by calculating the ratio of the area occupied by the largest urban block to the total urban area, known as the Largest Patch Index (LPI). The multi-index measurement method involves establishing a comprehensive evaluation index system using data from multiple dimensions, followed by a comprehensive assessment to determine UC.…”
Section: Literature Reviewmentioning
confidence: 99%